IMPLEMENTING MULTICULTURAL VALUES OF STUDENTS THROUGH RELIGIOUS CULTURE IN ELEMENTARY SCHOOL ISLAMIC GLOBAL SCHOOL MALANG CITY - Fausi, Ach Fikri (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2020)
Abstract: The internalization of multicultural values ​​is carried out as an effort to introduce the diversity of Indonesian society. This means that the internalization of multicultural values ​​wants to provide planting for students to respect and have good humanistic qualities among their peers. Internalization of values ​​is a way to introduce diversity and differences to students without questioning the differences that each student has. From the results of observations at SD-Islamic Global School Malang City, educators has properly applied multicultural internalization to students through religious culture. This discovery aims to obtain concrete, definite and accountable clarity regarding the internalization of multicultural values ​​to students through religious culture in SD-Islamic Global School Malang City. This study aims to: 1) Understand the religious culture model in SD-Islamic Global School Malang City, 2) identify multicultural values ​​internalized through religious culture in SD Islamic Global School Malang City, and 3) describe the process of internalizing multicultural values through religious culture in SD Islamic Global School Malang City. To achieve this goal, this study used a qualitative research approach by selecting the background of SD Islamic Global School Malang, then the researcher used a case study research type. The results showed that: 1) Religious culture model in SD-Islamic Global School Malang City is divided into two types, namely: a) the value of devotion to God, and b) human values. 2) There are two types of multicultural values ​​internalized through religious culture in SD-Islamic Global School Malang, namely: a) democratic values. b) The value of tolerance, 3) The process of internalizing the multicultural values ​​of students through religious culture at SD-Islamic Global School Malang: a) role models, teachers b) habits, and c) through Standard Operating Procedures (SOP).